Building Bridges: How Integrated STEM with Problem-Based Learning Can Enhance Student Critical Thinking and Learning Outcomes in Chemistry - Tairas*, Nelson; Salirawati, Das; Suyanta, Suyanta; Rohaeti, Eli; Haatainen, Maria Outi (Jurnal Pendidikan Sains Indonesia, 2024)
Low critical thinking skills and student learning outcomes are still widely found, especially in chemistry learning. This study aims to analyze the application of STEM integrated problem-based learning (PBL) on chemistry materials, and to analyze STEM-based learning integrated with PBL to improve students' critical thinking skills and learning outcomes on chemistry materials. The method used in this research is a systematic literature review based on articles traced through Google Schoolar, Garuda, and ERIC databases. The data obtained was then analysed descriptively. The results showed that: (1) From a number of STEM-PBL implementations that have been carried out in various fields, the implementation of STEM-PBL in chemistry learning obtained a percentage of 32%; (2) STEM-PBL implementation can improve students' critical thinking skills and learning outcomes ranging from moderate to high categories. STEM-PBL learning is effectively used to improve critical thinking skills and learning outcomes, so it can be used as an alternative in chemistry learning.